Jacobi Stability Analysis of Unified Chaotic System - Shukla, Vijay K.; Yadav, Vijay K.; Kumar, Abhishek; Mishra, Prashant K. (Discontinuity, Nonlinearity, and Complexity, 2026)
This article investigates Jacobi stability analysis of unified chaotic system. The stability analysis of unified system has been discussed by using the Kosambi-Cartan-Chern (KCC) theory, which is based on differential geometry. The unified system is transformed into a pair of second-order differential equations. The five KCC invariants are obtained to study the dynamics of unified chaotic system. The deviation curvature tensor is obtained and it explains the stability of the system. Further, the dynamics of unified chaotic system near the equilibrium points is also discussed.